Mechanical and Tribological Properties of Carbon Fiber/Glass Fiber-Reinforced Epoxy Hybrid Composites Filled with Al2O3 Particles - Kaykılarlı, Cantekin; Haydarov, Aymurat; Köse, Duygu; Yeprem, Hasibe Aygül (Hitit Üniversitesi, 2023)
In this study, we produced Aluminum oxide (Al2O3) reinforced carbon fiber and glass fiber reinforced polymer (CFRP, GFRP) composites and investigated mechanical and tribological properties. Al2O3 was dispersed in epoxy resin using a mechanical stirrer. The composites are produced via the hand lay-up method and dried at room temperature for 48 hours. The properties of composites were determined via Archimedes’ method, flexural, impact, hardness and wear tests. The highest flexural strength and hardness were found at 946.3 MPa and 48.7 HBA for 3 wt.% Al2O3 reinforced CFRP, respectively. The highest impact strength was observed at 187.4 kJ/m2 for an un-reinforced GFRP composite. The lowest Coefficient of Friction (COF) and wear depth was found 3 wt.% Al2O3 reinforced GFRP composites.
Keywords: Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler